A rare case report on complications in pregnancy with systemic lupus erythematosus in a post-renal transplant patient - Chavan, Niranjan N.; Ajmera, Darshana P.; Kapote, Deepali S.; Deshmukh, Prasad Y.; Sheriar, Zubin N.; Pathan, Zeba Haroon; Boob, Manan M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
To preview the feto-maternal outcome in post-renal transplant pregnant women with systemic lupus erythematosus (SLE). To distinguish preeclampsia from hypertension in renal transplant recipients as diagnosis is not always straightforward and all differentials need a thorough evaluation. Hypertension is a prevalent issue among kidney transplant recipients, with reported incidence rates ranging from 52% to 69%. Additionally, the occurrence of pre-eclampsia in renal transplant recipients falls within the range of 24% to 38%, demonstrating a significantly elevated risk compared to the 4-5% incidence rate seen in the general population. A 29-year-old female para 1 IUFD 1 abortion 1, in a known case of SLE with hypothyroidism with lupus nephritis with post renal transplant status with thrombocytopenia with preeclampsia with day 7 of emergency LSCS done in view of non-progress of labor with intrauterine fetal demise with abruptio placenta referred in view of query SLE flare or severe preeclamptic features with rectus sheath hematoma. Renal transplant restores fertility; thus, pregnancy requires careful planning and affected women should be managed in tertiary care obstetrics centers working in tight multidisciplinary cooperation with transplant physicians.